The myeloid sarcoma treated by Venetoclax with hypomethylating agent followed by stem cell transplantation: rare case report - Aleksina Shatilova; Larisa Girshova; Daniil Zaytsev; Irina Budaeva; Yuliya Mirolyubova; Darya Ryzhkova; Roman Grozov; Konstantin Bogdanov; Tatiana Nikulina; Dmitriy Motorin; Darina Zammoeva; Svetlana Efremova; et al. (BMC, 2021)
Abstract Background Myeloid sarcoma (MS) is a very rare condition, develops both in patients with other hematological neoplasms, and as isolated tumor. MS of the gynecologic tract is extremely rare. An available literature data about diagnosis and management of MS is summarized in the article. The role of chemotherapy, radiation therapy, surgery and bone marrow transplantation in the treatment is discussed. Polychemotherapy and allogeneic bone marrow transplantation were suggested to be the optimal treatment strategy of MS of the gynecological tract. The use of new targeted agents results in promising clinical data. Case presentation We are presenting a rare clinical case of a MS of the uterine cervix with concomitant bone marrow involvement and describe all the peculiarities of the clinical course, diagnosis, and treatment. The patient received chemotherapy followed by allogeneic bone marrow transplantation. The pre-transplant therapy allowed us to perform allogeneic bone marrow transplantation with the deepest response possible: complete PET-negative and MRD-negative remission of the disease. Conclusions MS remains a subject of discussion regarding its diagnostic and therapeutic aspects. The use of novel targeting agents can be perspective option for patient with extramedullary disease.